Türkiye`de yapılan tarih araştırmalarında Türklerin İslâm öncesi inanç dünyası üzerine görüşler (1923-1980) - Kaya, Aytaç (My University, 2015)
Türkiye`de tarih algısı XIX. yüzyılda Osmanlı ve İslâm tarihi üzerine düşünceler ile başlarken, XX. yüzyıla gelindiğinde ise İslâmiyet öncesi Türk tarihi de merak edilmeye başlanmıştır. Türklerin İslâmiyet öncesi inanç dünyası üzerine yazılar da, kablelislâm Türk tarihinin içinde kendine bir yer buldu. Çalışmada, cumhuriyetin kurulduğu 1923 tarihinden 1980`e kadar olan zaman diliminde Türklerin İslâmiyet öncesi inanç dünyası üzerine görüşler ele alındı. Söz konusu süreç, konunun Ziya Gökalp tarafından ciddi bir şekilde ele alınmaya başlamasından onu dinler tarihi araştırmaları dahilinde ele alan Hikmet Tanyu`nun çalışmalarına kadar gitmektedir. Görüşler dikkatle incelendiğinde, araştırmacıların bazı konularda ortak noktada buluşurken bazı konularda da farklı yaklaşımlara sahip olduğu ortaya çıkmaktadır. nanç Dünyası, Ziya Gökalp, Hikmet Tanyu, Şamanizm, Gök Tanrı.

The conception of history in Turkey begins with the thoughts about Ottoman Empire and Islamic History in the 19th century, however When it comes to he 20th century, people began to wonder about Turkish history before Islam. Writings about belief system of Turkish people before Islam, had a wide coverage in the Turkish history before Islam. The work covered arguments about religious life and spiritual thoughts of Turkish people before Islam, from the establishment of republic, to the year 1980. The process that being talked about, begins from the Ziya Gökalp’s significant efforts to investigate the topic and continues with Hikmet Tanyu who approaches it in the perspective of history of Religions. when we analyze the different approaches carefully, it reveals that researchers share the same opinions on some subjects while they differ on others. Key Words: The Belief System, Ziya Gökalp, Hikmet Tanyu, Shamanism, Sky God.
Keywords: Tarih (Ortaçağ); Türkiye